Ethnography of Science: A Literature Review - Diastuti, Indah Mei; Ahmadi, Anas (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The study of how certain communities or ethnic groups perceive and comprehend science is known as ethnoscience. This discipline investigates how various communities use, comprehend, and interpret science. While some communities could be more skeptics and hesitant to adopt new science and technology, others might be more receptive to both. Beliefs, culture, and religion may all have an impact on how society applies science. In addition, ethnoscience investigates the ways in which science affects society. An educational strategy called ethnoscience links the actual knowledge of a society to scientific understanding . It is a new type of ethnography that allows cultural researchers to develop grassroots ideas based on ethno and folk without necessarily accepting western cultural theories that may be irrelevant.Ethnoscience is an interdisciplinary field of study that combines the principles of ethnography and science. This field aims to understand the relationship between culture and science. This article discusses the origins of ethnoscience, the scope of the field of ethnoscience studies, and the future of ethnoscience. Ethnoscience encompasses a variety of scientific disciplines, including anthropology, sociology, history, and philosophy of science. One of the main research areas in ethnoscience is the study of indigenous knowledge systems. Ethnoscience also studies the relationship between science and religion. Ethnoscience can help us understand how scientific knowledge is produced and used in different cultural contexts.